Zearalenone toxins produced by some species of Fusarium (NTU Journal of Agriculture and Veterinary Science, 2024)
Mycotoxins or fungal toxins are secondary metabolism comounds of filamentous fungi that are released at the end of the growth phase of particular species of Fusarium spp., Aspergillus spp., Penicillium spp. They are generated in hot and humid conditions. These toxins are included the most usual groups of food pollutants. Of the 400 kinds of mycotoxins identified, about 20 of them are considered a global threat to human being and animal health. Because these toxins can modify the food chain in different stages of planting, collecting, packing and processing. Zearalenone is a kind of mycotoxin created by the fungi Fusarium genus. They are found more in grains for instance corn, barley, wheat, oats and sorghum and have estrogenic effects on different organisms. Zeralenone is quickly absorbed and by binding to estrogen receptors, it disrupts the quantity of reproductive hormones. In this article, we review information on zearalenone generated by certain Fusarium species.